(untitled) (Current Problems in Rail Vehicles, 2025)
Solid lubricants, applied to flanges of rail vehicles by bogie-mounted devices, comprise one of the tools for reducing friction and wear at the interface of the flange and the rail gauge face. For testing these lubricants, a standard methodology using a twin-disc machine is available. Test results are affected by various factors, of which this paper deals with the application force of the lubricant sample. The experiments result not only in the identification of this effect, but also – in the context of other published results – an explanation of the phenomena that take place at the interface of the test discs and that determine the development of the friction coefficient during the test.